2018
DOI: 10.4149/neo_2018_170112n25
|View full text |Cite
|
Sign up to set email alerts
|

miR-506 suppresses cervical cancer cell proliferation both in vitro and in vivo

Abstract: Cervical cancer (CC) is one of the most common gynecological malignancies in women worldwide. Recently increasing evidences indicate aberrant expression of miR-506 was reported to be associated with a variety of tumors. The aimof this study was to evaluate the potential role of miR-506 in CC and verify its effect on the regulation of ABCC4. The expression of miR-506 in cervical cancer tissues and HeLa and C33A cell lines was examined using quantitative Real-time PCR. MTT assay and animals studies were use to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…In human and clinical cervical cancer cell specimens (HeLa and C33A), significant downregulation of miR-506 was reported compared to that of matched cell lines and adjacent normal tissues. Further analyzes revealed the potential use of miR-506 in suppressing the proliferation of cervical cancer cells [9]. In gastric cancer, miR-506 was found to suppress metastatic invasion and angiogenesis by targeting ETS1 [10].…”
Section: Introductionmentioning
confidence: 99%
“…In human and clinical cervical cancer cell specimens (HeLa and C33A), significant downregulation of miR-506 was reported compared to that of matched cell lines and adjacent normal tissues. Further analyzes revealed the potential use of miR-506 in suppressing the proliferation of cervical cancer cells [9]. In gastric cancer, miR-506 was found to suppress metastatic invasion and angiogenesis by targeting ETS1 [10].…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] For instance, Gong et al proved that miR-506 inhibited cervical cancer cell proliferation both in vitro and in vivo. [22][23][24] For instance, Gong et al proved that miR-506 inhibited cervical cancer cell proliferation both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…miR-506 has been reported to play a suppressive role in several human tumors including gastric cancer, cervical cancer, and colorectal cancer. [22][23][24] For instance, Gong et al proved that miR-506 inhibited cervical cancer cell proliferation both in vitro and in vivo. Besides, Lei et al 25 reported that miR-506 regulated cell proliferation via downregulating iASPP expression in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of RSC on RANKL-induced osteoclastogenesis was examined by He and colleagues 17 . Additional assessment demonstrated the possible application of miR-506 in repressing the proliferation of cervical cancer cells 22 . The transition from epithelium to mesenchymal cells was modulated by miR-506 in breast cancer cells 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable miR-506 downregulation was revealed in cervical cancer cell samples (C33A and HeLa) compared with that of control cells and the surrounding normal tissues. Additional assessment demonstrated the possible application of miR-506 in repressing the proliferation of cervical cancer cells 22 . It was discovered that miR-506 repressed metastatic invasion as well as vessel generation by targeting ETS1 in gastric cancer 23…”
Section: Introductionmentioning
confidence: 99%